MONITORING OF ANTIBIOTIC RESIDUES IN BROILER CHICKEN LIVERS IN TABANAN REGENCY, BALI - Arinata, I Ketut Teguh; Tenaya, I Wayan Masa; Agustina, Kadek Karang; Besung, I Nengah Kerta; Sudira, I Wayan; Suardana, Ida Bagus Kade (Buletin Veteriner Udayana, 2026)
Antibiotic residues in animal products can pose health risks, including antimicrobial resistance, allergies, and toxicity. The use of antibiotics in inappropriate doses, either excessive or insufficient, can cause antibiotic residues in animal products, especially in the liver, milk, and meat. Broiler chicken livers have a higher risk of residue accumulation than other organs due to their role in drug metabolism. This study aims to determine the presence or absence of antibiotic residues in broiler chicken livers in relation to the level of knowledge and attitudes of farmers regarding the use of antibiotics administered during the broiler chicken rearing process in Tabanan Regency, Bali. This study is observational with a purposive sampling method that requires 20 broiler chicken liver samples, and data on farmers' knowledge and attitudes regarding antibiotic use is obtained directly through interviews from broiler chicken farms. Antibiotic residues in broiler chicken liver samples will be tested using a screening test based on the Kirby-Bauer method at the Denpasar Veterinary Public Health Laboratory. The research data was tabulated and analyzed descriptively, both qualitatively and quantitatively. The test results showed that all broiler chicken liver samples were negative for antibiotic residues. These results were supported by the farmers' high level of knowledge regarding the proper use of antibiotics, compliance with withdrawal periods, and the application of doses that were generally in accordance with recommendations. Although all farmers still reported using antibiotics during rearing, the pattern of administration was monitored and found to be controlled and not excessive. It is hoped that these good attitudes and practices can be maintained in order to ensure the safety of poultry-derived food.